PENERAPAN GOOGLE FORM SEBAGAI ALAT EVALUASI PEMBELAJARAN DI SD N 5 KEDIRI - Wayan, Juliawan; Ni Wayan Suastini; Ni Komang Sri Yuliastini; I Wayan Susanta; Roro Dwi Umi Badriah; Kadek Suharditha (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
This community service activity was carried out at SD N 5 Kediri, located at Jl. Melati No.6, Kediri, Kediri District, Tabanan Regency. The purpose of this activity was to provide socialization and share knowledge about the use of one of Google's applications, Google Forms, which can facilitate teachers in assessment or evaluation systems. Traditionally conducted in class using paper, these assessments are replaced with a sophisticated application that can be downloaded for free online. The data collection technique used in this activity was through questionnaires. The socialization activity organized by the community service team at SD N 5 Kediri, in collaboration with the teachers, received positive feedback as it helped teachers understand the use of information technology and the application of Google Forms for evaluating students' learning progress.